Hormonal Regulation of Stem Cell Proliferation at the Arabidopsis thaliana Root Stem Cell Niche - García-Gómez, Mónica L.; Garay-Arroyo, Adriana; García-Ponce, Berenice; Sánchez, María de la Paz; Álvarez-Buylla, Elena R. (Frontiers in Plant Science, 2021)
The root stem cell niche (SCN) of Arabidopsis thaliana consists of the quiescent center (QC) cells and the surrounding initial stem cells that produce progeny to replenish all the tissues of the root. The QC cells divide rather slowly relative to the initials, yet most root tissues can be formed from these cells depending on the requirements of the plant. Hormones are fundamental cues that link such needs with the cell proliferation and differentiation dynamics at the root SCN. Nonetheless, the crosstalk between hormones signaling and the mechanisms that regulate developmental adjustments is still not fully understood. Developmental transcriptional regulatory networks modulate hormone biosynthesis, metabolism and signaling, and conversely hormonal responses can affect the expression of transcription factors involved in the spatiotemporal patterning at the root SCN. Hence, a complex genetic-hormonal regulatory network underlies root patterning, growth and plasticity in response to changing environmental conditions. In this review we summarize the scientific literature regarding the role of hormones in the regulation of QC cell proliferation and discuss how hormonal signaling pathways may be integrated with the gene regulatory network that underlies cell fate in the root SCN. The conceptual framework we present aims to contribute to the understanding of the mechanisms by which hormonal pathways act as integrators of environmental cues to impact SCN activity.